An Investigation of the Necessity of Information Retrieval for Algorithms for Full-Text Arabic Databases - Moukdad, Haidar (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This research investigated one aspect of Arabic linguistic structure that might affect information retrieval: prefixes and their role in word formation. This aspect of Arabic information retrieval was looked at in an English environment. The lack of left-hand truncation in English search engines was hypothesized to hinder the effectiveness of retrieving information in Arabic, and search experiments were. . .